UNDERSTANDING OF PHYSICAL THERAPISTS AND PREPAREDNESS OF PHYSICAL THERAPY TELEREHABILITATION IN BANGKOK AND VICINITY: MUSCULOSKELETAL SYSTEM - Winairuk, Thitimard; Rattanavichit, Yupaporn; Boonsinsukh, Rumpa; Kitiyanant, Kasima (Srinakharinwirot University Journal of Sciences and Technology, 2024)
Nowadays technologies have been adopted to improve patient access to rehabilitation services in the form of PT telerehabilitation to reduce the spread of COVID-19. The services require physical therapists’ understanding and hospital preparedness. However, currently, there is no survey on such information from hospitals in Bangkok and outskirts of Bangkok, the areas with high population density and technology accessibility. This research aimed to study the level of physical therapists’ understanding and preparedness for PT telerehabilitation services of hospitals in Bangkok and outskirts of Bangkok for patients with musculoskeletal problems. The study was conducted based on exploratory research design using a questionnaire on Google Form. Respondents were physical therapists who specialize in musculoskeletal system of hospitals in Bangkok and outskirts of Bangkok. The findings from the study showed that among 163 physical therapists who responded to the questionnaire, 100 persons came from private hospitals and 63 persons came from government hospitals. It was found that the physical therapists had overall understanding about PT telerehabilitation services at a high level except the understanding in the types of PT telerehabilitation which was in moderate level. They understood laws and elements for services the most. They had overall preparedness at a moderate level. In conclusion, to support PT telerehabilitation to gain more efficiency, physical therapists should be developed to have knowledge and understanding about types of PT telerehabilitation services so that they will be able to select appropriate service types that meet each patient. Besides, technology system for services should be developed as well as communication, places where services are provided to achieve more efficiency in caring for patients.